2017
DOI: 10.1016/j.jmii.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of immunization with pneumococcal conjugated vaccines on Streptococcus pneumoniae resistance patterns in acute otitis media

Abstract: Following the introduction of 7- and 13-pneumococcal conjugate vaccines (PCVs) in Israel, we demonstrated that within Streptococcus pneumoniae (Sp) positive middle ear cultures, obtained from young children with severe acute otitis media (AOM) episodes, there were more penicillin-susceptible and less multi-drug resistant Sp isolates in PCV immunized children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…[ 5 – 8 ] Recent studies had raised concerns with S pneumoniae developing resistance against penicillin and other antibiotics. [ 47 , 48 ] Contrary to this, the results of the present study showed only 5.2% of S pneumoniae positive episodes to have complete resistance to penicillin, which is in line with previous studies conducted in Chile, Colombia, Mexico, and Costa Rica. [ 21 , 22 , 25 , 26 , 31 33 , 40 , 41 ]…”
Section: Discussionsupporting
confidence: 90%
“…[ 5 – 8 ] Recent studies had raised concerns with S pneumoniae developing resistance against penicillin and other antibiotics. [ 47 , 48 ] Contrary to this, the results of the present study showed only 5.2% of S pneumoniae positive episodes to have complete resistance to penicillin, which is in line with previous studies conducted in Chile, Colombia, Mexico, and Costa Rica. [ 21 , 22 , 25 , 26 , 31 33 , 40 , 41 ]…”
Section: Discussionsupporting
confidence: 90%
“…Recommending amoxicillin as the first-line therapy has been found to positively affect the resistance patterns of Streptococcus pneumoniae isolated from middle ear fluid or AOM-associated otorrhoea in French and Israeli PCV immunised children 24 25. Disagreement on the dosage and duration of antibiotic therapy were noted in the studied guidelines.…”
Section: Discussionmentioning
confidence: 98%
“…In contrast, countries that implemented AOM guidelines have already reported reduced rates of appropriate antibiotic prescription for AOM and low resistance rates in isolated pathogens 24 25 31…”
Section: Discussionmentioning
confidence: 99%
“…6,11,12,15 This decline is largely due to a dramatic decrease in cases of AOM attributable to S. pneumoniae (including pen-R S. pneumoniae ) as documented both in the U.S., 6,14,16 Iceland 17 and Israel (south and central). 1113 Going hand-in-hand with these observations are reports from Israel, 18 France 7,19 and the U.S. 6,8,20 indicating there is a substantial decrease in nasopharyngeal colonization with vaccine strains of S. pneumoniae with a relative increase in non-vaccine strains. In all but one of these studies, 8 there was a concurrent decrease in penicillin and ceftriaxone resistant strains of S. pneumoniae .…”
Section: Current Data On Microbiology Of Aom and Nasopharyngeal Colonmentioning
confidence: 88%
“…6,1012 With the decrease of nasopharyngeal colonization with vaccine strains, there has also been a decrease in AOM caused by pen-R S. pneumoniae . 13,14 Both of these observations underscore the basic principle that nasopharyngeal colonization with S. pneumoniae is a necessary prelude to the development of either AOM or ABS with that organism.…”
Section: Bacteriology Of Aom and Abs And Impact Of Pneumococcal Conjumentioning
confidence: 89%